2013
DOI: 10.1016/j.jsb.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the ParM filament at 8.5Å resolution

Abstract: The actin-like protein ParM forms the cytomotive filament of the ParMRC system, a type II plasmid segregation system encoded by Escherichia coli R1 plasmid. We report an 8.5 Å resolution reconstruction of the ParM filament, obtained using cryo-electron microscopy. Fitting of the 3D density reconstruction with monomeric crystal structures of ParM provides insights into dynamic instability of ParM filaments. The structural analysis suggests that a ParM conformation, corresponding to a metastable state, is held w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…From the ΔCcMreBdh co-crystal structures with ADP and AMPPNP, it is clear that the active site could well accommodate a guanidine instead of an adenine as the major contacts are with the ribose and phosphate moieties of the nucleotide, a feature, again, shared with ParM (Gayathri et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…From the ΔCcMreBdh co-crystal structures with ADP and AMPPNP, it is clear that the active site could well accommodate a guanidine instead of an adenine as the major contacts are with the ribose and phosphate moieties of the nucleotide, a feature, again, shared with ParM (Gayathri et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…S3), which was surprising if it is assumed that they formed similar filaments. A paper reporting a reconstruction of a ParM filament (33) has suggested that there is a conservation of subunit-subunit contacts between ParM and actin, but this involves arguments such as that residues in a helix in ParM (Arg257 and Lys258) are equivalent to residues in a loop in actin (Glu270 and Gly268) that has the opposite polarity, raising questions about this equivalence. When ParM is aligned to actin and the longitudinal interfacial residues in both are mapped onto this alignment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These highly divergent ParM amino acid sequences ( Fig. 1) have recently been shown to translate into equally divergent filament architectures (Gayathri et al, 2013;Popp et al, 2010a;Popp et al, 2012;Popp et al, 2010b), which adds some weight to the hypothesis that an element of positive selection to diverge might have existed between selected ParMs.…”
Section: Bacterial Actinsmentioning
confidence: 93%
“…For instance, the timing and location of assembly of the plasmid-segregation filament ParM will be different to those required for cell wall synthesis and cell division, and thus for MreB and FtsA. The divergence of the bacterial actins has ensured that they will form independent homopolymers, as protomer interfaces and helical parameters are variable among the classes of actin-like filaments (Gayathri et al, 2013;Popp and Robinson, 2011;Szwedziak et al, 2012;van den Ent et al, 2001). Thus accomplishment of a specific biological function has provided the context in which the host actins (MreB and FtsA) have diverged and have become optimized for their specialized function.…”
Section: Bacterial Actinsmentioning
confidence: 99%